2010
DOI: 10.1002/marc.200900799
|View full text |Cite
|
Sign up to set email alerts
|

Colloid‐Assisted Self‐Assembly of Robust, Three‐Dimensional Networks of Carbon Nanotubes over Large Areas

Abstract: Natural materials, such as bone and spider silk, possess remarkable properties as a result of sophisticated nanoscale structuring. They have inspired the design of synthetic materials whose structure at the nanoscale is carefully engineered or where nanoparticles, such as rods or wires, are self-assembled. Although much work has been done in recent years to create ordered structures using diblock copolymers and template-assisted assembly, no reports describe highly ordered, three-dimensional nanotube arrays wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 31 publications
(30 reference statements)
1
18
0
Order By: Relevance
“…Based on our previous findings,14 we have created ordered monolayers of monodispersed colloidal particles containing honeycomb‐like networks of CNTs. In our previous work, we have shown that in three dimensions, such precise assembly of CNTs is facilitated by tuning the interface between the polymer and the CNTs using a nonionic surfactant.…”
Section: The Values Of the Linear Expansion Coefficients For Various mentioning
confidence: 99%
“…Based on our previous findings,14 we have created ordered monolayers of monodispersed colloidal particles containing honeycomb‐like networks of CNTs. In our previous work, we have shown that in three dimensions, such precise assembly of CNTs is facilitated by tuning the interface between the polymer and the CNTs using a nonionic surfactant.…”
Section: The Values Of the Linear Expansion Coefficients For Various mentioning
confidence: 99%
“…It is apparent that the polymer particles undergo deformation, becoming more elongated in the direction of applied stress (Figures 2B-E). In previous work, we have shown qualitatively that for 3D composites, there is a resulting mapping of the nanotube assembly with polymer deformation (Jurewicz et al, 2010).…”
Section: Understanding the Stress Transfer Between Cnt Bundles Lockedmentioning
confidence: 70%
“…Therefore, for this work, we have chosen two composites containing either 0.2, 0.5, or 1 wt.% of SWNTs in the final dry samples. For SWNTlatex composite films in this concentration regime, we expect to see SWNT bundles forming complete networks within the latex crystal template well above the electrical percolation threshold (Jurewicz et al, 2010). Moreover, at large strain levels, these composites maintain their viscoelastic properties and still conduct electricity.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations